ANALYSIS OF LANGUAGE STYLE FOUND IN ESPN FC INDONESIA NET TELEVISION - Anugerahadi Afrianton; Hamzah Hamzah (Universitas Negeri Padang, 2017)
The research aimed to find the types of language style and communication accommodation tendency used by football observer in Indonesia. The source of data in this research is ESPN FC Indonesia at episode June 18th 2016. This research focused on language style used by speakers of ESPN FC Indonesia. The writer used descriptive method which is describing the phenomenon based on the source of data. This research analyzed the conversation to find the types of language style and communication accommodation tendency in ESPN FC Indonesia. On the analysis, the writer found that there are four language styles namely formal, consultative, casual, and intimate. Then, consultative style is the mostly language style used by the speakers with percentage is about 50%. Furthermore, the writer found that there are two strategies in communication accommodation tendency namely convergence and divergence. In addition, convergence is the mostly strategy used by the speakers of ESPN Indonesia with percentage is about 58%.